Application of Canva Media in Entrepreneurship Project to Strengthen Pancasila Student Profile - Sirlanie, Angela; Suryandari, Kartika Christy; Sukarno, Sukarno (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to evaluate the effectiveness of Canva as a digital design medium in the implementation of the Pancasila Student Profile Strengthening Project (P5) with an entrepreneurship theme in elementary education. Methodology: The research investigates how Canva facilitates students' character development, particularly in creativity, independence, collaboration, and critical thinking. Employing a descriptive qualitative approach within a case study design, the study involved classroom observations, in-depth interviews with school stakeholders, and documentation analysis of student work. Data triangulation and thematic narrative analysis were used to ensure validity and richness of interpretation. Main Findings: The findings indicate that Canva significantly enhances students' engagement and character formation, supporting active, collaborative, and visually expressive learning. Teachers observed improved student autonomy and creativity, while students expressed pride and satisfaction in their work. Despite challenges such as limited device access and uneven digital literacy, adaptive strategies enabled inclusive participation. Novelty/Originality of this study: The originality of this study lies in integrating a graphic design-based platform into project-based character education aligned with the Pancasila Profile framework. The results contribute to empirical insights on innovative and culturally grounded digital learning practices for primary education in the 21st century.